PENGARUH PEMASARAN MELALUI MEDIA SOCIAL, KESADARAN MEREK, ELECTRONIC WORD OF MOUTH TERHADAP MINAT PEMBELIAN SURVEI PADA PRODUK ALINSKIE BROTHERS - Yapto Tottan (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
This study aims to determine the effect of marketing through social media, brand awareness, electronic word of mouth on the interest in purchasing surveys on Alinsky brothers' products. The object of this research is social media users in Jakarta. This research-based on formal research and use questionnaires for collecting the information to 110 peoples. There are some analyst techniques used in this research, such as validity and reliability test, descriptive statistical analysis, and classic assumptions test. For the multiple regression analysis, use model test (F Test), variable test (t-test), and determination coefficient test (R2). Based on the research, found enough evidence to stated that Social Media Marketing, Brand Awareness, and Electronic Word of Mouth have a positive impact to purchase intention.Keywords: Media Social Marketing, Brand Awareness, Electronic Word of Mouth, PurchaseIntention